P/s : Sửa đề : Cho x > y > 1 và x5 + y5 = x - y . Chứng minh rằng : x4 + y4 < 1
+)Ta có : x4 + y4 < x4 + x3y + x2y2 + xy3 + y4
Mà x > y > 1 \( \implies\) x - y > 0
\( \implies\) ( x - y ) ( x4 + y4 ) < ( x - y ) ( x4 + x3y + x2y2 + xy3 + y4 ) ( * )
+)Ta có : ( x - y ) ( x4 + x3y + x2y2 + xy3 + y4 )
= x ( x4 + x3y + x2y2 + xy3 + y4 ) - y ( x4 + x3y + x2y2 + xy3 + y4 )
= x5 + x4y + x3y2 + x2y3 + xy4 - x4y - x3y2 - x2y3 - xy4 - y5
= x5 - y5
\( \implies\) ( x - y ) ( x4 + x3y + x2y2 + xy3 + y4 ) = x5 - y5 ( ** )
Từ ( * ) ; ( ** )
\( \implies\) ( x - y ) ( x4 + y4 ) < x5 - y5
Mà x5 - y5 < x5 + y5
\( \implies\) ( x - y ) ( x4 + y4 ) < x5 - y5
\( \implies\) ( x - y ) ( x4 + y4 ) < x - y
\( \implies\) x4 + y4 < 1 ( đpcm )